La grammaire à base sémantique: une conception «bâtie» et non pas «donnée». Quelques remarques sur le changement de la compréhension de certaines notions fondamentales dans la théorie de Stanisław Karolak - Hrabia, Michał (Neophilologica, 2011)
The aim of this paper is to demonstrate the evolution of the semantic-based grammar of Stanisław Karolak. The main attention is focused on the three fundamental concepts of the theory: predicate-argument structures, elementary sentences and thematic-rhematic structures. The author also attempts to prove that, despite multiple modifications, the general idea of the theory has never radically changed.